Candidatus Methylumidiphilus Drives Peaks in Methanotrophic Relative Abundance in Stratified Lakes and Ponds Across Northern Landscapes - Martin, Gaëtan; Rissanen, Antti J.; Garcia, Sarahi L.; Mehrshad, Maliheh; Buck, Moritz; Peura, Sari (Frontiers in Microbiology, 2021)
Boreal lakes and ponds produce two thirds of the total natural methane emissions above the latitude of 50° North. These emissions are regulated by methanotrophs who oxidize up to 90 % of the methane produced in the sediments and the water column. Despite their importance, the diversity and distribution of the methanotroph in lakes is still poorly understood. Here, we explored the diversity and distribution of methanotrophs in 40 oxygen stratified water bodies in boreal and subarctic areas in Europe and North America. In our data, gammaproteobacterial methanotrophs (order Methylococcales) dominated the methanotrophic communities throughout the water columns. A recently discovered lineage of Methylococcales, Candidatus Methylumidiphilus, was present in all of the studied water bodies. Alphaproteobacterial methanotrophs were the second most abundant group of methanotrophs and in the top layer of the lakes, characterized by low CH4 concentration, their abundance could even surpass the abundance of the gammaproteobacterial methanotrophs. We argue that this reflects the high affinity of the alphaproteobacterial methanotrophs for CH4 and support the idea that they can be considered as stress tolerant strategists and the gammaproteobacterial methanotrophs as competitive strategists. In addition, relative abundances of anaerobic methanotrophs Candidatus Methanoperedenaceae and Candidatus Methylomirabilis, were strongly correlated, suggesting possible co-metabolism. Our data also suggest that these anaerobic methanotrophs could be active in oxic layers. In non-metric multidimensional scaling alpha- and gammaproteobacterial methanotrophs formed separate clusters based on their abundances in the samples, except for gammaproteobacterial Candidatus Methylumidiphilus, which was separated from these two clusters. This may reflect similarities in the niche and environmental requirements of the different genera within alpha- and gammaproteobacterial methanotrophs. Our study confirms the importance of O2 and CH4 in shaping the methanotrophic communities and further suggests that one single variable cannot explain the diversity and distribution of the methanotrophs, but instead, those are regulated by lake specific factors.